The Effect Of Price, Product Quality, And Brand Image On Purchase Decisions And Its Implications On Consumer Loyalty (Survey Of Lcgc Automotive Consumers In Greater Tangerang) - Ahmad Nurhadi; Umi Narimawati; Popo Suryana; Sidik Priadana; Jaja Suteja (International Journal of Social Sciences, 2026)
The Low Cost Green Car(LCGC) automotive industry in Indonesia has experienced significant growth along with the increasing public demand for affordable and environmentally friendly vehicles. Intensifying competition has encouraged manufacturers to better understand the factors influencing consumer behavior, particularly in purchasing decision-making and loyalty formation. This study aims to analyze the effects of price, product quality, and brand image on purchasing decisions and their implications for consumer loyalty in the LCGC automotive market in the Tangerang Raya area. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to LCGC vehicle consumers in Tangerang Raya using purposive sampling techniques. Data analysis was conducted using Structural Equation Modeling (SEM) to examine both direct and indirect relationships among the research variables. The results indicate that price, product quality, and brand image have a positive and significant effect on purchasing decisions. Furthermore, purchasing decisions have a positive and significant impact on consumer loyalty. The findings also reveal that purchasing decisions mediate the relationship between price, product quality, and brand image and consumer loyalty. This study provides managerial implications for LCGC automotive manufacturers and marketers to implement competitive pricing strategies, enhance product quality, and strengthen brand image in order to encourage purchasing decisions and foster sustainable consumer loyalty.